2013
DOI: 10.1039/c3cp50916h
|View full text |Cite
|
Sign up to set email alerts
|

Design of a nanocarrier with regulated drug release ability utilizing a reversible conformational transition of a peptide, responsive to slight changes in pH

Abstract: We investigated the drug releasing behavior of a novel nanocarrier system, utilizing a peptide to act as a nanogate to the mesopore, on a mesoporous silica nanoparticle. The surface peptide on mesoporous silica displayed pH-dependant mesopore cap-uncap switching behavior, enabled by the reversible β-sheet-to-random coil conformational transition resulting from slight pH changes between 8.0 and 6.0. The peptide adopted a β-sheet structure under weakly basic conditions (pH 8.0) and a random coil conformation und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Adenine DNA has been used as a capping agent taking advantage of the instability of the non-Watson–Crick secondary structures when the pH drops [ 205 ]. Double DNA strands formed by the interaction of thymine bases with Hg 2+ ions that suffer the phase transition to single strand when the pH drops have also been reported [ 206 ], as well as small peptides that suffer the β-sheet-to-random coil transition [ 207 ].…”
Section: Supramolecular Structures As Pore-capping Agentsmentioning
confidence: 99%
“…Adenine DNA has been used as a capping agent taking advantage of the instability of the non-Watson–Crick secondary structures when the pH drops [ 205 ]. Double DNA strands formed by the interaction of thymine bases with Hg 2+ ions that suffer the phase transition to single strand when the pH drops have also been reported [ 206 ], as well as small peptides that suffer the β-sheet-to-random coil transition [ 207 ].…”
Section: Supramolecular Structures As Pore-capping Agentsmentioning
confidence: 99%
“…pH‐dependent conformational transition of peptides may be suitable for the mesopore cap–uncap switching behavior. As the proof of concept, Kato's group demonstrated that a DDS utilized the pH‐sensitive reversible conformational transition peptide (Ac‐(VKVS) 4 E‐NH 2 ) as the gatekeeper of MSN . The peptide of a β‐sheet structure under weakly basic conditions (pH 8.0) could transform to a random coil conformation under weakly acidic conditions (pH 6.0).…”
Section: Stimuli‐responsive Peptidesmentioning
confidence: 99%
“…Nanocarriers that are highly sensitive to surrounding conditions (pH, temperature, concentration of biomolecules in the affected area, among others)h ave been actively studied as a base for several medical research areas, such as regenerative medicine, [1][2][3] drug delivery, [4][5][6][7][8] and gene therapy. [9,10] Nanocarriers are especially important in the research for new drug delivery systems, with the aim of improving patients' quality of life and reducing ad rug's side effects.…”
Section: Introductionmentioning
confidence: 99%